Humanizing processes after harm part 1: patient safety incident investigations, litigation and the experiences of those affected - Ramsey, Lauren; Sheard, Laura; Waring, Justin; McHugh, Siobhan; Simms-Ellis, Ruth; Louch, Gemma; Ludwin, Katherine; O’Hara, Jane K. (Frontiers in Health Services, 2025)
BackgroundThere is a growing international policy focus on involving those affected by healthcare safety incidents, in subsequent investigations. Nonetheless, there remains little UK-based evidence exploring how this relates to the experiences of those affected over time, including the factors influencing decisions to litigate.AimsWe aimed to explore the experiences of patients, families, staff and legal representatives affected by safety incidents over time, and the factors influencing decisions to litigate.MethodsParticipants were purposively recruited via (i) communication from four NHS hospital Trusts or an independent national investigator in England, (ii) relevant charitable organizations, (iii) social media, and (iv) word of mouth to take part in a qualitative semi-structured interview study. Data were analyzed using an inductive reflexive thematic approach.Findings42 people with personal or professional experience of safety incident investigations participated, comprising patients and families (n = 18), healthcare staff (n = 7), legal staff (n = 1), and investigators (n = 16). Patients and families started investigation processes with cautious hope, but over time, came to realize that they lacked power, knowledge, and support to navigate the system, made clear in awaited investigation reports. Systemic fear of litigation not only failed to meet the needs of those affected, but also inadvertently led to some pursuing litigation. Staff had parallel experiences of exclusion, lacking support and feeling left with an incomplete narrative. Importantly, investigating was often perceived as a lonely, invisible and undervalued role involving skilled “work” with limited training, resources, and infrastructure. Ultimately, elusive “organizational agendas” were prioritized above the needs of all affected.ConclusionsIncident investigations fail to acknowledge and address emotional distress experienced by all affected, resulting in compounded harm. To address this, we propose five key recommendations, to: (1) prioritize the needs of those affected by incidents, (2) overcome culturally engrained fears of litigation to re-humanize processes and reduce rates of unnecessary litigation, (3) recognize and value the emotionally laborious and skilled work of investigators (4) inform and support those affected, (5) proceed in ways that recognize and seek to reduce social inequities.